Education fractions in pedagogical periodical in Lithuania between the two word wars - Ragalytė, Birutė; Paukštienė, Alma (Lietuvos matematikos rinkinys, 2011)
Teaching fractions in periodical between the two word wars are introduced in article. The problems of education fractions are analyzed. Methods how reflect the actions of fractions are described.